Loss Aversion and Hybrid Entrepreneurship: Economic Insecurity, Low-Income Wage Work, and Side Hustles - Shahriar, Abu Zafar M.; Shepherd, Dean A.; Zaman, Rayhan Ara (Entrepreneurship Theory and Practice, 2026)
Hybrid entrepreneurship as a side hustle is a widespread yet understudied coping strategy among low-income wage workers. This study examines how loss aversion is associated with such side-hustle activities and their links to well-being. We conducted a mixed-method study in Bangladesh. Quantitative analysis, based on surveys and lab experiments, indicates that loss aversion is associated with a higher likelihood of engaging in hybrid entrepreneurship, which is in turn linked to higher well-being. Qualitative analysis, based on in-depth interviews, illustrates mechanisms that may underlie these associations. Together, these findings provide insights into the protective role of hybrid entrepreneurship in poverty contexts.